المكتبة الإلكترونية ودورها في ترقية خدمات المعلومات - د. منهل عبد المجيد يوسف محمد علي (White Nile Journal for Studies and Research, 2014)
This research aims to make users aquatinted with the role played by electronic library in information service development and libraries to convert its manual systems in to electronic ones. To achieve these goals and to give historical background of electronic library and information technology the documentary and historical methods were used. In addition to these methods the analytical and enumerative methods were used to measure the user's acceptance of electronic information services and role of electronic library in services promotion. For data collecting questionnaire was distributed and the information obtained is analyzed and evaluate in tables. Some of results obtained are the interaction between computer technologies. And communication technology has created a new technology of information dissemination such as networking, international data bases and electronic library. And the traditional library services still play key role comparable with the electronic one. The study has come to several recommendations such as the traditional libraries should be encouraged to convert its manual system into the electronic one. And users should be trained to use the electronic library. And electronic library should be taught as part of the university curricula.